FRI0469 Measuring Outcome in Psoriatic Arthritis (MOPSA), A New Web-Based Tool for Assessment of Psoriatic Arthritis Showing Initiation of Treatment Change in Patients Achieving Minimal Disease Activity. (15th July 2016) - Elmamoun, M.; Szentpetery, A.; Gallagher, P.; FitzGerald, O.
Abstract : Background: Psoriatic arthritis (PsA) is a heterogeneous disease that includes features of peripheral arthritis, spondylitis, dactylitis, enthesitis, and skin and nail disease. PsA affects about 30% of patients with psoriasis. 1 Minimal Disease Activity (MDA) is defined as a patient acceptable disease state which is validated and increasingly recognised as a treatment target. MDA is defined when a patient has 5 of the following 7 criteria: tender joint count ≤1, swollen joint count ≤1, tender entheseal point ≤1, PASI ≤1 or body surface area ≤3%, Pain Visual analogue score (VAS) ≤15, patient global ≤20, Health Assessment Questionnaire ≤0.5. 2 Composite Psoriatic Disease Activity Index (CPDAI) assesses the five domains in PsA. Within each domain a score (range 0–3) is assigned according to predefined cut-offs. The scores for each domain are then added together to give a final score range of 0–15, 0 for no disease and 15 for severe disease. 3 Recently, Measuring Outcome in Psoriatic Arthritis (MOPsA), a new web-based tool for assessment of PsA was developed and is freely available to use (see https://mopsa.ie ). MOPSA will calculate all the scores and determine both MDA and CPDAI. MOPSA provides a graphic representation of CPDAI in the form of a spidergram that can be compared with subsequent visits. Objectives: Our aim was to assess, (1) disease activity using CPDAI and the percentage of patients reaching MDA, in consecutive cohort of established PsA patients attending our unit; and (2) whether treatment change was initiated based on MDA state. Methods: 137 patients with PsA, fulfilling CASPAR criteria, were included in this study. 68 tender joint counts (TJC) and 66 swollen joint counts (SJC) were recorded. Skin scores included Dermatology Quality of Life Index (DLQI), Body Surface Area (BSA) and Psoriasis Area Severity Index (PASI). Patient reported outcome measures (PROMs) included: Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Health Assessment Questionnaire (HAQ), Ankylosing Spondylitis Quality of Life (ASQoL). CPDAI was calculated and MDA status was assessed. Results: The mean age was 46.1 (± 11.6) and 72 (52.6%) were females. Clinical outcome measures and PROMs are shown in table 1 . The mean CPDAI score was 3.75 (± 2.94); 52 (37%) patients reached MDA. Of the 85 patients not in MDA, CPDAI was 5.94 ± 3 in the 37 who had a treatment change and 4.54 ± 2.49 in the 48 who did not. Of those undergoing treatment changes, 7 patients started on biologics, 4 switched to another biologic and 3 had their dose increased. 6 were started on synthetic DMARD, 2 had a second DMARD added to their regimen, and 8 had their dose increased. 6 patients had a short course of systemic steroids while 12 patients had intra-articular steroids injections. Conclusions: MOPsA gives a comprehensive assessment of psoriatic disease that can be followed longitudinally. One third of patients in our cohort achieved MDA. CPDAI was higher in those patients not achieving MDA status where treatment was changed. References: Mease PJ, et al. J Am Acad Dermatol. 2013, 69(5):729–35 Coates LC, et al. Ann Rheum Dis. 2010, 69:48–53 Mumtaz A, et al. Ann Rheum Dis. 2011, 70(2):272–7 Disclosure of Interest: M. Elmamoun: None declared, A. Szentpetery: None declared, P. Gallagher: None declared, O. FitzGerald Grant/research support from: Pfizer, AbbVie, BMS, UCB, Consultant for: Pfizer, AbbVie, Janssen, MSD, Cellgene, Novartis, Speakers bureau: Pfizer, AbbVie, Janssen, Cellgene